Models of information exchange for UK telehealth systems - Adeogun, Oluseun; Tiwari, Ashutosh; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2011)
Aim: The aim of the paper was to identify the models of information exchange for UKtelehealth systems.Methodology: Twelve telehealth offerings were evaluated and models representing theinformation exchange routes were constructed. Questionnaires were used to validate thediagrammatical representations of the models with a response rate of 55%.Results: The models were classified as possessing four sections: preparing for data transfer,data transfer, information generation and information transfer from health professional topatient.In preparing for data transfer, basic data entry was automated in most systems thoughadditional inputs (i.e. information about diet, lifestyle and medication) could be enteredbefore the data was sent into the telehealth system. For the data transfer aspect, results andadditional inputs were sent to intermediate devices, which were connectors between pointof-care devices, patients and health professionals. Data were then forwarded to either a webportal, a remote database or a monitoring/call centre. Information generation was eitherthrough computational methods or through the expertise of health professionals. Informationtransfer to the patient occurred in four forms: email, telehealth monitor message, textmessage or phone call.Conclusion: On comparing the models, three generic models were outlined. Five differentforms of information exchange between users of the system were identified: patientpush,system-stimulation, dialogue, health professional-pull and observation. Patient-pushand health professional-pull are the dominant themes from the telehealth offeringsevaluated.